A Buck-Chopper Based Energy Storage System for the Cascaded H-Bridge Inverters in PV Applications. (July 2018) - Vavilapalli, Sridhar; Umashankar, S.; Sanjeevikumar, P.; Fedák, Viliam; Mihet-Popa, Lucian; Ramachandaramurthy, Vigna K.
Abstract: Cascaded H-Bridge (CHB) inverter configuration is most suitable for high power solar inverters. In this work, various energy storage system (ESS) configurations suitable for CHB inverters such as AC side coupled ESS, Dual active bridge based ESS, and buck-chopper and bi-directional chopper based ESS configurations are discussed. Comparison of these configurations on the basis of cost, control complexity, controller hardware requirements are carried out and the advantages of Buck-chopper based ESS systems are listed. Operation and the dynamic response of the buck-chopper based systems are explained in detail with the help of simulation results.